GAYA BAHASA PADA LIRIK LAGU “TULUS HATI LUHUR BUDI” CIPTAAN H. RHOMA IRAMA - Ali Manshur; Syafi’ Junadi (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2021)
This study aims to describe the use of language style in the lyrics of the song "Tulus Hati Sublime Budi". This research is in the form of a qualitative descriptive. The method used is content analysis. The source of the data is a document in the form of the lyrics of the song "Tulus Hati Luhur Budi". The data collection technique was carried out by listening and recording techniques, because the data source was in the form of text. The validity test used in this study is triangulation theory, which is a method of research on the same topic using different theories in analyzing data. The data analysis technique used in this study uses flow analysis, which includes three components, namely: data reduction; (2) data presentation; (3) drawing conclusions. Based on the results of the study, it can be concluded that in the lyrics of the song "Tulus Hati Luhur Budi" the latest single Rhoma Irama feat Rita Sugiartoo there are language styles, including repetition language style (Epikuzueksis, Anafora, and Epistropha), personification language style, metaphor language style, and style. Simile language.